Influência da purificação do extrato ácido na pectina extraída do mesocarpo da maçã - Cruz, Amanda Rosa da (2023)
Currently, there are several environmental problems, such as the accumulation of non-renewable materials and the wrong management of agro-industrial waste. Strategies to minimize the damage caused to nature are necessary. Pectin has thickening and stabilizing characteristics, and its extraction is usually carried out at high temperatures and in an acid medium. When extracted from waste without purification treatment, such as apple pomace, pectin includes other components, such as sugars and phenolic compounds in the precipitation process. Thus, this work aimed to observe the influence of acid extract purification on biofilms with pectin extracted from apple mesocarp, comparing two different types of vacuum filtration: conventional through synthetic tissue and through a layer of microcrystalline cellulose. The analyzes performed on the extracted pectin samples were yield; pH; degree of esterification; and viscosity. The average yield obtained was 16.1% with conventional filtration and 17.2% with microcrystalline cellulose. The pH values obtained after extraction using high methoxylation commercial pectin was pH = 3 with standard deviation of 0.03 and low methoxylation was pH = 3.1 with standard deviation of 0.07. Using conventional bench pectin and microcrystalline filtration, the same pH = 1.4 was obtained with a standard deviation of 0.09 and 0.06, respectively. For conventional bench pectin, a degree esterification (DE) of 54.1 was obtained and with microcrystalline cellulose, a DE of 77.2, which is a considerable difference. As for commercial pectin’s, a smaller difference was obtained; high methoxylation pectin with DE of 74.2 and low methoxylation with DE of 64.2. Finally, comparing viscosity values for benchtop pectin’s, the conventional one was obtained with a viscosity of 1.26 and microcrystalline cellulose 1.31. While for commercial pectin’s with high methoxylation it was obtained a viscosity of 1.20 and low methoxylation of 1.11, reaching results of lower viscosity using commercial pectin’s although not an expressive difference.